Amplification of heat extremes by plant CO2 physiological forcing - Christopher B. Skinner; Christopher J. Poulsen; Justin S. Mankin (Nature Communications, 2018)
The effect of plants on future extreme heat events under elevated carbon dioxide (CO2) is unclear. Here, the authors show that CO2 plant physiological effects lead to increases in heat waves within a suite of climate model simulations, suggesting that vegetated areas are at risk of increased heat extremes.